ONLINE HEDONIC CONSUMERS’ PRIVACY AWATENESS AND PRIVACY PARADOX: A SYSTEMATIC LITERATURE REVIEW - FG. M. Shafayet Ullah; Sameer Kumar; Fumitaka Furuoka (Malaysian Journal of Business and Economics (MJBE), 2022)
The purpose of this paper is to provide a comprehensive review of the literature on Online Hedonic Consumers’ Privacy Paradox and Privacy Awareness. Furthermore, the authors attempt to identify a gap that can be addressed in the future by developing a comprehensive and integrated model on Online Hedonic Consumer Behaviour that focuses on their Privacy Awareness. The authors conducted a systematic literature review of the extant literature. The discussion on “Privacy”, “Privacy Paradox” and “Privacy Awareness” elucidated the differences among them, thereby helping to remove any confusions held by the researchers and readers. This review offered insight into the current status of research in this field and recognized the factor “Privacy Awareness” as a gap in the existing model on Online Hedonic Consumer Behaviour that could properly be explored in further scholarly empirical research. Managers and E-Commerce vendors could utilize the findings of this review to address their Hedonic Consumer Privacy Awareness for the growth of their online businesses. This paper lays a groundwork to explore Online Hedonic Consumer Privacy Awareness in detail. A new integrated model is suggested, which will lead to the development of a theoretical framework for researchers to further examine the mediation effect of Privacy Awareness.